Power management in microgrid through PV system / Ameerul A. J. Jeman, Naeem M. S. Hannoon and Sharon S. Gerang - Jeman, Ameerul A. J.; Hannoon, Naeem M.S; Gerang, Sharon S. (UiTM Press, 2020)
This paper presents a performance comparison of real and reactive power flow in microgrid through PV system using both controller which are Fuzzy logic based and Conventional controller. In general, an electrical power management is an electronic system that provides detail information about the power flow in a distribution generation system or power substation. The PV system has two major problems; namely, low conversion efficiency of electric power generation and the amount electric power generated by solar array changes continuously. Therefore, the objective of this paper is to analyse the controller performance of conventional controller and the proposed one. The early work in fuzzy control was motivated by a desire to directly express the control actions of an experienced human operator in the controller and to obtain smooth interpolation between discrete controller outputs. Conventional controllers are simple and easy to understand but it is not very efficient due to presence of non-linearity in the system while fuzzy controllers have proper actions like human control actions, needs less data storage and more robust. The PV system will be simulated by using MATLAB/Simulink respectively. The results of the controller performance will be presented and compared with similar cases. Based on the results that are going to be obtained, a better performance in the fuzzy controller than the conventional controller is expected.